Childhood obesity in Mexico: Influencing factors and prevention strategies - Shamah-Levy, Teresa; Cuevas-Nasu, Lucia; Gaona-Pineda, Elsa B.; Valenzuela-Bravo, Danae G.; Méndez Gómez-Humarán, Ignacio; Ávila-Arcos, Marco A. (Frontiers in Public Health, 2022)
Background Overweight and obesity in school-age children, in Mexico as in other countries around the world, is a rapidly increasing public health problem within recent years, with important consequences for the future health of the population. Various national strategies at the individual and community level have been established to prevent these conditions, but none have yet succeeded. Objective To describe factors which influence overweight and obesity in school-age children five to 11 years old in Mexico, and national strategies for the prevention and management of these conditions. Methods The data herein is derived from six National Health and Nutrition Surveys in Mexico: 2006, 2012, 2016, 2018, 2020, and 2021. They include a total of 45,216 school-age children with complete anthropometric data (weight/height) distributed over 84 pseudo-panels defined by age, wellbeing condition class (WCC), gender, and type of locality of residence. The indicators calculated were overweight and obesity by body mass index according to World Health Organization guidelines. Predictors are food consumption indicators in five groups. Results The prevalence of overweight and obesity showed a positive linear trend (p < 0.001), with average annual increases of 0.41%. Increases in fruit consumption reduced the prevalence of these conditions by 6.6% (p = 0.01) and vegetable consumption reduced this by 8.3%. Conclusions Overweight and obesity in school-age children is a growing problem with serious repercussions for future life. New strategies are needed which focus on involving food systems, which translates to healthy and sustainable diets.